Topical Antibiotic Treatment in Dermatology - Matthew Dallo; Kavina Patel; Adelaide A. Hebert (MDPI AG, 2023)
Many indications in dermatology can be effectively managed with topical antibiotics, including acne vulgaris, wound infections, secondarily infected dermatitis, and impetigo. Dermatologists must be familiar with the wide spectrum of topical antibiotics available, including indications, mechanisms of action, adverse events, and spectra of activity. Dermatologists must also keep antibiotic resistance in mind when utilizing these medications. Due to the widespread use of topical antibiotics and their importance in dermatology, a literature review was performed using a systematic search of PubMed and Google Scholar with the terms topical antibiotics, skin infections, dermatology, antimicrobials, and inflammatory dermatoses to identify English-language articles published between 1965-2022 from any country. Relevant publications were manually reviewed for additional content. The following literature review will summarize the common topical antibiotics used in dermatology.